Pengaruh Aktivitas Fisik Terhadap Indeks Massa Tubuh Wanita Usia Subur Pengguna Kontrasepsi Hormonal Di Masa Pandemi Covid-19: The Influence Of Physical Activity On The Body Mass Index Of Women Of Reproductive Age Using Hormonal Contraception In The Covid-19 Pandemic - Martha Winingsih; Ni Wayan Noviani (Media Publikasi Penelitian Kebidanan, 2023)
The use of hormonal contraception for women of childbearing age (WUS) can trigger weight gain. In addition, the enactment of the social restriction policy during the Covid-19 pandemic has reduced physical activity for WUS and has a risk of weight gain and obesity. Weight problems to the occurrence of obesity can trigger health problems. The general objective of this study was to determine the physical activity and body mass index (BMI) of WUS users of hormonal contraception during the Covid-19 pandemic. The specific objectives of this study were to identify physical activity, body mass index and to determine the effect of physical activity on the BMI of women of childbearing age using hormonal contraception during the Covid-19 pandemic. Physical activity data collection was carried out on 30 respondents through interviews with a questionnaire guide referring to the Short-Form version of the International Physical Activity Questionnaire (IPAQ-SF). Body Mass Index (BMI) is calculated using the approach of body weight and height. Observational data were analyzed using Kendall's Rank Correlation test. The results showed that most of the physical activity of WUS had moderate activity, reaching 63.33%. The body mass index for WUS is mostly normal, namely 63.33% and the obese category is 36.67%. The results of the correlation test showed that there was a significant effect between physical activity and BMI of women of childbearing age using hormonal contraception, with a significance value of 0.000 <0.01